Studying the impact of business re-engineering on operational performance and the modifying role of management with intelligence in a number of mineral water production plants in the Kurdistan Region of Iraq - Osman Karim Mahmoud (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The research aims to study the extent of wich the operational performance is affected by business re-engineering and the moderation role of the management by intelligences in that impact in factories producing mineral water. The research hypotheses were set according to its objectives. (77) Questionnaire form was distributed to managers, officials and heads of people in the factories producing mineral water out of population (95) with confidence level (95%) and margin of error (5%) and retrieved a total of 74 forms of which 72 of it were valid for analysis while two forms were removed. A number of statistical methods were employed to prove the validity of the research hypotheses such as mean, standard deviation, percentage verification and multiple hierarchical regressions to measure the role of the moderator variable. The results of the analysis provided approves for the hypotheses to propose a set of conclusions accordingly, the most important of which is that the researched factories are concerned with the dimensions of business re-engineering in order to improve operational performance and that the management by intelligence in the researched factories have a moderating role in moderating the positive impact of re-engineering business in operational performance, as well as Providing a set of recommendations, the most important of which are: The researched factories should pay adequate attention to the various intelligences of strategic, emotional and competitive as well as the re-engineering of the business in order to achieve its objectives of improving operational efficiency and effectiveness and thus enhancing operational Performance continuously.